Strategic talent management : creating the right workforce - Greene, Robert J. (Robert James), 1940- (New York: Routledge, 2020)
"Clearly written and providing actionable strategies, this book explores new paradigms for workforce management to enable human resource managers and the organizations where they work to thrive in today's turbulent business environment. Robert Greene goes beyond the many human resource management books currently available, to deal head-on with the new realities of talent management, including such factors as the 'gig economy' and globalization. The book focuses on attracting, developing, and effectively utilizing human capital. It begins with human capital planning, and then explores strategies and programs that can attract and retain the workforce an organization needs. A range of sizes and types of organizations and different working relationships are considered, as Greene demonstrates how to evaluate the effectiveness of strategies that fit specific contexts and will sustain the viability of an organization's workforce into the future. Postgraduate students of human resource management, as well as current HR professionals and managers, will find this practical book an indispensable resource. PowerPoint slides and test banks are available to support instructors"--
Human capital planning -- Determining talent requirements -- Sourcing talent -- Selecting talent -- Utilizing the talent of employees -- Utilizing talent from outside sources -- Developing talent -- Talent management in the public sector -- Talent management for occupational groups -- Talent management in the future.
Includes bibliographical references and index.
Keywords: Personnel management